2017
DOI: 10.1186/s12974-017-0960-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of dorsal horn cannabinoid CB2 receptor suppresses the expression of P2Y12 and P2Y13 receptors in neuropathic pain rats

Abstract: BackgroundMore evidence suggests that dorsal spinal cord microglia is an important site contributing to CB2 receptor-mediated analgesia. The upregulation of P2Y12 and P2Y13 purinoceptors in spinal dorsal horn microglia is involved in the development of pain behavior caused by peripheral nerve injury. However, it is not known whether the expression of P2Y12 and P2Y13 receptors at spinal dorsal horn will be influenced after CB2 receptor activation in neuropathic pain rats.MethodsChronic constriction injury (CCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Therefore, it is possible that shortened travel distance in central area of P2Y 12 KO mice might be caused by reduced overall locomotor activities (see Figure S1, Supporting Information). Moreover, as overwhelming evidences indicate an important role for P2Y 12 in neuropathic pain, we chose more than one mild test, respectively, to measure the performance of the mice, but we could not completely exclude the possibility that the sensory impairments could affect behavior of KO animals in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that shortened travel distance in central area of P2Y 12 KO mice might be caused by reduced overall locomotor activities (see Figure S1, Supporting Information). Moreover, as overwhelming evidences indicate an important role for P2Y 12 in neuropathic pain, we chose more than one mild test, respectively, to measure the performance of the mice, but we could not completely exclude the possibility that the sensory impairments could affect behavior of KO animals in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Haynes et al () and Stefani et al () found that, despite confirming P2Y 13 mRNA expression in microglia (Zhang et al, ), its expression could not be detected at the protein level. The inability to antibody‐label P2Y 13 may reflect a high rate of constitutive proteasomal degradation (Pons et al, ), or may alternatively suggest that P2Y 13 protein is only expressed at high levels in microglial culture (Quintas, Vale, Goncalves, & Queiroz, ) or upon microglial activation in situ (Niu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, P2Y 13 protein expression may be low (Haynes et al, 2006), possibly due to constitutive ubiquitination and proteasomal degradation (Pons et al, 2014). P2Y 13 mRNA is upregulated in pathological conditions such as demyelination (Bedard, Tremblay, Chernomoretz, & Vallieres, 2007) and neuropathic pain (Kobayashi, Yamanaka, Yanamoto, Okubo, & Noguchi, 2012;Niu et al, 2017), suggesting a role of this receptor in neuroinflammation. However, its function in microglia, especially under physiological conditions, is still unclear, although it may evoke a rise of [Ca 2+ ] i in response to ADP (Zeng et al, 2014) and be involved in the release of proinflammatory cytokines (Liu et al, 2017).…”
mentioning
confidence: 99%
“…Cannabis contains more than 60 endogenous and exogenous compounds defined as cannabinoids (CBs) that act primarily through specific cannabinoid receptors: CB 1 and CB 2 receptors. The CB 1 are distributed in the central nervous system and involved in learning, memory and cognitive processes, while the CB 2 receptors are located in the peripheral nervous system, including brainstem, cerebellum, microglia and the immune system . In the past decade, preclinical studies and case reports have shown the therapeutic potential of two main CBs, delta‐9‐tetrahydrocannabinol acid (Δ 9 ‐THCA) and cannabidiol (CBD) against a range of pathologies .…”
Section: Introductionmentioning
confidence: 99%
“…The CB 1 are distributed in the central nervous system and involved in learning, memory and cognitive processes, while the CB 2 receptors are located in the peripheral nervous system, including brainstem, cerebellum, microglia and the immune system. [8][9][10][11][12][13][14][15] In the past decade, preclinical studies and case reports have shown the therapeutic potential of two main CBs, delta-9tetrahydrocannabinol acid (D 9 -THCA) and cannabidiol (CBD) against a range of pathologies. [16,17] D 9 -THCA is the main constituent in raw cannabis, it converts to D 9 -THC when heated over a certain temperature, binding at both CB receptors.…”
Section: Introductionmentioning
confidence: 99%